2010
DOI: 10.1007/s10661-010-1414-7
|View full text |Cite
|
Sign up to set email alerts
|

Stagnant surface water bodies (SSWBs) as an alternative water resource for the Chittagong metropolitan area of Bangladesh: physicochemical characterization in terms of water quality indices

Abstract: 1The concern over ensuing fresh water scarcity has forced the developing countries to delve 2 for alternative water resources. In this study we examined the potential of stagnant surface 3 water bodies (SSWBs) as alternative fresh water resources in the densely populated 4Chittagong metropolitan area (CMPA) of Bangladesh -where there is an acute shortage of 5 urban fresh water supply. Water samples, collected at one month intervals for a period of one 6 year from 12 stations distributed over the whole metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(41 reference statements)
1
8
0
3
Order By: Relevance
“…This simple index was reported to be comparable to two other indices of 20 parameters for the assessment of water body under the influence of industrial discharge [28]; nonetheless, there is a tendency of overestimation as the parameters are assigned with similar weightage [29,30]. As observed, water quality depicted with WQI min covers a wide spectrum from Class I to Class V with index values ranging between 10 and 82.…”
Section: Assessment Of Water Quality Indexsupporting
confidence: 55%
“…This simple index was reported to be comparable to two other indices of 20 parameters for the assessment of water body under the influence of industrial discharge [28]; nonetheless, there is a tendency of overestimation as the parameters are assigned with similar weightage [29,30]. As observed, water quality depicted with WQI min covers a wide spectrum from Class I to Class V with index values ranging between 10 and 82.…”
Section: Assessment Of Water Quality Indexsupporting
confidence: 55%
“…Another study conducted in Ghana [5] also found concentrations of lead, uranium and boron above the World Health Organisation (WHO) Guide Values (GVs) in restricted areas. Low metallic content was observed for most water samples analysed in Bangladesh [6]. Adekunle et al [7] showed that in some rural settlements in Nigeria most of the water samples from hand-dug wells, in the residential areas near the municipal dumps, contained Pb and Cd above the WHO limits for drinking water.…”
Section: Introductionmentioning
confidence: 96%
“…Also iron and manganese can be present in surface and ground waters at levels ranging from 0.5 to 50 mg/L and from 1 μg/L to 10 mg/L, respectively [8]. Concentrations exceeding WHO GVs, respectively 0.3 mg Fe/L and 0.4 mg Mn/L, were found in Cambodia [3], Zimbabwe [9], Ghana [4,5], Cameroon [10], Pakistan [11] and Bangladesh [6]. Sharaky et al [12] observed in the groundwater in the Nile delta area concentrations of trace elements lower than the standard limits, except for iron, manganese and nickel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma é necessário preservá-la e utilizá-la racionalmente (BECKER, 2008;RAHMAN, et al, 2011;FERREIRA;ROCHA;FIGUEIREDO, 2015).…”
Section: Introductionunclassified